Ethnosport: Concept, Theory and Development - Turdimuratov Yangiboy Allamuratovich (Scientific Trends, 2025)
This article examines the definitions of the concept of “ethnosport” presented in the scientific literature, as well as its theoretical foundations and the role of ethnosport in modern processes of globalization, its role in the processes of preserving ethnic identity is updated. In addition, information is provided on international organizations and projects that make a significant contribution to the popularization of types of ethnosport.
Keywords: Sport, ethnosport, sportization, theory, UNESCO, ethnomovement, traditional games, events, organization, world ethnosport, Challenge, World Nomad Games, confederation.